Green synthesis and characterization of iron oxide nanoparticles: evaluation of the reactivity of their surfaces - Ahmouda, Kaouthar (Universty of Eloued جامعة الشهيد حمه لخضر, 2022)
الملخص: في هاته الاطروحة تمّ تقديم دراستين جديدتين، الأولى بحثت في كيفية تأثير قوة مضادّات الأكسدة في إرجاع كاتيونات الحديد الثلاثية على الفراغات الكاتيونّية Fe2+ (العيوب) المتشكّلة داخل جزيئات الوستيت النّانوية (FexO) المصنّعة بطريقة التوليف الأخضر. في الدراسة الثانية، بعد أكسدة الوستيت كليا وتحوّله إلى جزيئات الماغنيتيت (Fe3O4) النّانوية في الشروط الطبيعية، تمّت دراسة تأثير حمضّية المستخلص النباتي المائي المستخدم في التوليف الأخضر لجزيئات الماغنيتيت على فاعلية سطوح عيّنات الماغنيتيت في الامتزاز التفضيلي والمُحسّن للمُلّون أخضر المثيل خلال ثلاثة أطوار متتالية: في الطور الأوّل امتزاز أخضر المثيل في الشروط الطبيعية في الظلام، في الطور الثاني، التحفيز الحراري في الظلام لمحلول أخضر المثيل/Fe3O4 المتبقّي، وأخيرا في الطور الثالث، التحفيز الضوئي بواسطة الأشعة فوق البنفسجية لمحلول أخضر المثيل/Fe3O4 المتبقّي بعد التحفيز بالحرارة. أُستخدم في هاته الدراسة أربعة مستخلصات نباتية مائية وملح كلور الحديد الثلاثي في التوليف الأخضر لجزيئات الوستيت. النباتات التي تمّ استخدامها في هاته الدراسة هي: العرعر، القريطفة، الإكليل، والشيح، قوة حمضية (pH) هاته المستخلصات النباتية هي على التوالي؛ 3.69، 4.63، 5.05، و5.25. تم توصيف جميع العيّنات المصنّعة بـ انعراج الأشعة السنية (XRD)، المجهر الإلكتروني الماسح، الأشعة تحت الحمراء، والأشعة فوق البنفسجية. بالنسبة إلى عيّنات FexO، تمّ حساب الثوابت الشبكية من خلال معطيات أطياف الأشعة السينية، ثم تمّ حساب ستوكيومترية كاتيونات الحديد الثنائي في تركيبة الوستيت باستخدام معادلة McCammon. أظهرت نتائج الدراسة الأولى أن ال FRAP له تأثير واضح على تشكل العيوب والفراغات داخل جزيئات الوستيت النانوية. حيث، تؤدّي الزيادة في ال FRAP إلى انخفاض عيوب الحديد الثنائي داخل جزئيات الوستيت وبالتالي زيادة قطر الحبيبات. علاوة على ذلك، أظهرت دراسة تأثير العيوب على الديناميكا الحرارية لتشكّل الوستيت أن الطاقة الحرّة لتشكل الوستيت تأثّرت بهذه العيوب ومن ثم بال FRAP. تكمن حداثة الدراسة الثانية في تسليط الضوء على تأثير المستخلصات النباتية الوسيطة في التوليف الأخضر لمختلف عيّنات الماغنيتيت على خصائصه الفيزيائية والكيميائية التي تؤثّر على الامتزاز التفضيلي والمُحسّن لأخضر المثيل. الخصائص المدروسة هي: وظائف مجموعات الهيدروكسيل على أسطح الماغنيتيت، قطر الحبيبات النّانوية، وطاقة فجوة النطاق. وُجد أنّ حموضة المستخلصات النباتية لها تأثير واضح على الخصائص الفيزيائية والكيميائية المدروسة لعينّات الماغنيتيت. أظهر تحليل أطياف الاشعة تحت الحمراء أن كثافة مجموعات الهيدروكسيل تختلف في عيّنات الماغنيتيت الأربع. علاوة على ذلك، يختلف قطر حبيبات عيّنات الماغنيتيت المحسوبة بناءً على معطيات أطياف الاشعة السينية من 29.27 إلى 41.49 نانومتر. أظهر تحليل أطياف الاشعة فوق البنفسجية لعيّنات الماغنيتيت الأربع أنّ طاقات فجوة النطاق المباشر المقدرة تتراوح من 2.87 إلى 2.97 إلكترون فولت. أظهرت النتائج التي تمّ الوصول إليها أنّ انخفاض حموضة المستخلصات النباتية الوسيطة في التوليف الأخضر يُؤدّي إلى زيادة كثافة مجموعات الهيدروكسيل الوظيفية على أسطح الماغنيتيت مما أدّى إلى زيادة سعة امتزاز ومردود أخضر المثيل في الطور الأوّل. وبالتالي كان امتزاز أخضر المثيل أكثر تفضّيلاً على أسطح الماغنيتيت المصنّع بوساطة مستخلصات نباتية ضعيفة الحمضية. علاوة على ذلك، تؤدّي زيادة حموضة المستخلصات النباتية إلى انخفاض قطر الحبيبات النّانوية وزيادة طاقة فجوة النطاق وبالتّالي إلى بطء زمن إعادة تركيب الأزواج الإلكترون / الفجوة عند إثارة الإلكترونات. لذلك، أظهر الماغنيتيت الذي تمّ تصنيعه من مستخلص نباتي أكثر حمضّية مزيدًا من الفاعلية الحرارية والضوئية في امتزاز أخضر المثيل. Résumé : فرنسية أو انجلزية In this thesis, two novel studies are presented, the first one investigated how the Ferrous Reducing Antioxidant Potential (FRAP) of aqueous plant extracts affects F e2+ vacancies (defects) formation within greenly synthesized w ̈ustite (FexO) nanoparticles. In the second study, after the complete oxidation of FexO NPs into F e3O4 NPs under ambient conditions, the influence of mediating plant extract’s acidity on magnetite surface reactivity has been studied in the preferential and enhanced adsorption of methyl green (MG) on the different greenly synthesized Fe3O4 surfaces by coupling three processes: MG adsorption in ambient dark conditions at the first process, at the second process, the thermocatalysis of MG/Fe3O4 residual solution, and finally the photocatalysis by UV irradiation of MG/F e3O4 residual solution after applying thermocatalysis. This study used four aqueous plant extracts as reducing agents with F eCl3 as a precursor to synthesize FexO NPs. The plants dealt with in this study are Rosemarinus Officinalis.(L), Juniperus Phoenicia.(L), Matricaria Pubescens.(L), and Artemisia Herba-alba.(L), and their acidic extracts pH are respectively; 5.25, 5.05, 4.63, and 3.69. All synthesized samples are characterized by XRD, SEM, ATR-FTIR, and UV-Vis. For FexO, lattice parameters are calculated through XRD data, and then w ̈ustite compositions are calculated using the McCammon equation. Results of the first study showed that the FRAP has a clear effect on Fe2+ vacancies formation within w ̈ustite NPs. Indeed, the increase in the FRAP leads to a decrease in Fe2+ defects within w ̈ustite NPs and consequently an increase in the grain size. Furthermore, studying iron vacancies’ effect on w ̈ustite formation thermodynamic showed that free energy of w ̈ustite formation ∆G0f FeO(x) is impacted by cation vacancies and hence by FRAP. The novelty of the second study lies in highlighting the influence of the mediating plant extract on magnetite physicochemical characteristics which impact the preferential and enhanced MG adsorption. Studied characteristics are: hydroxyl groups functionality on magnetite surfaces, grain size, and band gap energy. It was found that plant extract acidity has a clear effect on studied physicochemical characteristics of magnetite samples. The analysis of FTIR spectra showed that hydroxyl groups densities differ on the four magnetite samples. Furthermore, the calculated grain sizes of magnetite samples based on XRD spectra data vary from 29.27 to 41.49 nm. The analysis of UV-Vis spectra of the four magnetite samples showed that estimated direct band gap energies vary from 2.87 to 2.97 eV. Found results showed that the decrease of mediating plant extract’s acidity leads to an increase in functional hydroxyl groups density on magnetite surfaces which conducted to an increase in MG adsorption capacity and yield in the first process. Thus, MG adsorption was more preferred on magnetite surfaces mediated by low acidic plant extracts. Furthermore, the increase of plant extract acidity leads to a decrease in particle size and an increase in band gap energy and therefore to the slowness of electron/hole pairs recombination lifetime upon electrons excitation. So, magnetite greenly synthesized from more acidic mediating plant extract showed more thermo- and photocatalytic activities in MG adsorption. MG adsorption under thermo- and photocatalysis processes were more enhanced on magnetite NPs exhibiting slower electron/hole pairs recombination lifetime.
أطروحة دكتوراه تخصص هندسة كيميائية في العلوم التكنولوجيا
Keywords: نانو أكسيد الحديد, ,F RAP الفراغات الكاتيونية, التوليف الأخضر, الامتزاز, أخضر المثيل, التحفيز الحراري, التحفيز الضوئي; iron oxide nanoparticles, FRAP, cation vacancies, green synthesis, adsorption, methyl green, thermocatalysis, photocatalysis